Obtaining triplet-triplet absorption spectra and triplet lifetimes of long-lived molecules with a UV-Visible spectrophotometer - Palmeira, Tiago (2024)
A simple method for obtaining triplet-triplet absorption (TTA) spectra and triplet state (T1) lifetimes of long-lived triplets is presented and demonstrated with the polycyclic aromatic hydrocarbon coronene (both normal and perdeuterated forms) in a polymer matrix at room temperature. The TTA spectra obtained with a camera flash and a spectrophotometer are noisier but otherwise identical to those obtained with a state-of-the-art flash photolysis apparatus. The triplet lifetimes obtained from transient absorption are identical to the phosphorescence lifetimes of the same samples.